An introduction to market & social research planning & using research tools & techniques - Adams, Karen; Brace, Ian 1949- (London Philadelphia Kogan Page, 2006)
An Introduction to Market and Social Research is an easy -to-use guide for anyone who needs to understand the basic principles and techniques of effective market or social research This step-by-step textbook contains clear descriptions, practical examples and activities that will help you to gain a clear understanding of the research process and how research information can be used effectivily in business decision making. A vital study guide for those working towards the MRS/City & Guilds Certificate in Market & Social Research, it follows the syllabus and contains regular revision sections to help candidates study for the exam. Key topics covered include: introducing market research; defingin research objectives; selecting a research design; identifying different research methods; understanding how sampling works; using quantitative research methods; using qualitative research methods; designing the questionaire; analysing research data; reporting and communicating research findings; developing your career in market research
Introduction to market research -- Why do I need research? Introducing market research -- What do I need to know? Defining research objectives -- How am I going to do it? Selecting a research design -- How can I gather information? Identifying different research methods -- Designing a research project: the tools of market research -- Who should I talk to? Understanding how sampling works -- Where can I find the data I need? Using quantitative research methods -- How can I find out what people feel about issues? Using qualitative research methods -- What questions should I ask? Designing the questionnaire -- Completing a market research project -- How do I know what it all means? Analysing research data -- What do I do with the information? Reporting and communicating research findings -- Where do I go from here? Developing your career in market research -- Test Yourself -- Task Answer Guide
Includes bibliographical references (p. [149]) and index
1
NEW, APPLIED_SC
Keywords: Marketing research